Evaluation of fungicides for the control of wheat rusts - Goulart, Augusto César Pereira; Paiva, Fernando de Assis (Pesquisa Agropecuaria Brasileira, 1991)
The control of leaf rust (Puccinia recondita f. sp. tritici) and stem rust (P. graminis f. sp. tritici) in wheat was evaluated under field conditions, in 1989, for the cultivar IAPAR 6-Tapejara. Eight triazole fungicides, singly or in mixture with mancozeb, prochloraz + fempropemorph, iminoctadine, two formulations of mancozeb, singly or in mixture with fentin hidroxide, were sprayed when the first rust symptoms appeared. The fungicides RH-7592 (fenethanil) 125 g a.i./ha, prochloraz + fempropemorph 450 + 750, flutriafol 125, etiltrianol 250, propiconazole 125, ciproconazole 100, triadimenol + mancozeb 125 + 2,000, flusilazole + mancozeb 125 + 2,000, flusilazole 125 and flutriafol + mancozeb 125 + 1,600, reduced more than 88% of rust symptoms. The propiconazole 62,5 and propiconazole + mancozeb 62,5 + 2,000 gave lower control than propiconazole 125. The two mancozeb formulations (water and flowable powders) gave similar results, with poor control. Higher yield, test weight and 1,000 seeds weight were obtained with the fungicides treatments.
Keywords: chemical control; Puccinia recondita f. sp. tritici; Puccinia graminis f. sp. tritici